Interpretation of signs and markers in Whiteboard Journal writing in forming political communication for the 2024 Presidential Election - Fadillah, Dani; Gita Pertiwi, Indah (Universitas Ahmad Dahlan, 2024)
This research aims to examine how political communication messages are conveyed to the public through social media portals. Utilizing a qualitative approach with content analysis as the method, this study investigates posts from the Instagram account @whiteboardjournal. The analysis process is carried out objectively and systematically using semiotic theory, especially Ferdinand de Saussure's concepts of